Michel Foucault and the Critique of Humanism - Alshiyab , Mohammad Khalid (Dirasat: Human and Social Sciences, 2023)
Objectives: This research aims to discuss the problem of humanism in Western philosophy and analyze its manifestations and investigate its theoretical sources through Foucault’s philosophy and his writings that criticize humanism. Methods: The study deeply analyzed and questioned Michel Foucault’s speech and examined its critical readings. Results: Foucault showed a new tendency that was concerned with self, truth, reason, knowledge, and human will. He realized that man is something within other things, and that his birth is not birth in the biological concept, rather man is mentally born, and this can be recognized through his words and the things he produces. Thus, Foucault’s speech showed that man is predetermined by inevitability. His death in Structuralism indicates the death of Man in the Middle Ages and the emergence of a new man with new knowledge. This man does not change things himself, but there are certain factors within the structure that work on changing him and determine his ways of thinking. Conclusions: The study recommends emphasizing the role of the self and its impact and human commitment toward human issues and human society, although man is governed by specific patterns that make him respond to the prevailing or dominant thought.